Antiplasmodial activity of methanol leaf extract of Citrus aurantifolia (Christm) Swingle - Ette Ettebong; Peace Ubulom; Aniekeme Etuk (Shahrekord University of Medical Sciences, 2019)
Introduction: Citrus aurantifolia (Christm) is a plant used for the treatment of various ailments including malaria. This study aimed to evaluate the in vivo antiplasmodial efficacy of methanol leaf extract of C. aurantifolia in Swiss albino mice. Methods: The median lethal dose (LD50) was determined by intraperitoneal administration of different doses of the extract (100-4000 mg/kg) to 6 groups of 3 mice each and the animals were observed for 24 hours for physical signs of toxicity. To evaluate the antiplasmodial activity of the extract, three models were used: suppressive, curative and repository. Doses of the extract used were 320, 640 and 960 mg/kg/d in mice, with Chloroquine (5 mg/kg/d) as standard drug. Pyrimethamine (1.2 mg/kg/d) was used as the standard drug for the repository test and distilled water (10 mL/kg/d) as control in all models. Results: In all models, the low dose (320 mg/kg) of the extract produced the highest chemosuppressive effects in all models (P < 0.001). Mice treated with extract lived longer than those in the control group (P < 0.001). Phytochemical screening revealed the presence of alkaloids, flavonoids, saponins, tannins and cardiac glycosides and the LD50 of 3280 mg/kg ± 0.01 shows that the extract has low toxicity. Conclusion: The result of this study shows that C. aurantifolia has antiplasmodial properties which support its use in ethnomedicine in the treatment of malaria.